2023
DOI: 10.3389/fnagi.2023.1102809
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the role of blood-brain barrier in Alzheimer’s disease: From delivery to target

Abstract: The existence of a selective blood-brain barrier (BBB) and neurovascular coupling are two unique central nervous system vasculature features that result in an intimate relationship between neurons, glia, and blood vessels. This leads to a significant pathophysiological overlap between neurodegenerative and cerebrovascular diseases. Alzheimer’s disease (AD) is the most prevalent neurodegenerative disease whose pathogenesis is still to be unveiled but has mostly been explored under the light of the amyloid-casca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 158 publications
0
11
0
Order By: Relevance
“…Here, we detected the potentially therapeutic immunomodulatory effects of selected Cu­(btsc) on AD iBEC, implicating additional neuroprotective mechanisms that may be involved at the level of BBB. Intriguingly, Cu­(btsc) were previously shown to exert therapeutic effects on preclinical models of AD, amyotrophic lateral sclerosis (ALS), and Parkinson’s disease (PD), as well as in first-in-human clinical trials targeting ALS and PD, all being neurodegenerative diseases with established roles in BBB neuroinflammation. Correspondingly, with BBB disruption becoming in itself an emerging drug target in neurodegeneration, further studies performed in our patient-derived model may support the ongoing efforts in identifying compounds that can improve cerebrovascular integrity in AD via active regulation of BEC and accelerate the translation of those therapies to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we detected the potentially therapeutic immunomodulatory effects of selected Cu­(btsc) on AD iBEC, implicating additional neuroprotective mechanisms that may be involved at the level of BBB. Intriguingly, Cu­(btsc) were previously shown to exert therapeutic effects on preclinical models of AD, amyotrophic lateral sclerosis (ALS), and Parkinson’s disease (PD), as well as in first-in-human clinical trials targeting ALS and PD, all being neurodegenerative diseases with established roles in BBB neuroinflammation. Correspondingly, with BBB disruption becoming in itself an emerging drug target in neurodegeneration, further studies performed in our patient-derived model may support the ongoing efforts in identifying compounds that can improve cerebrovascular integrity in AD via active regulation of BEC and accelerate the translation of those therapies to patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, growing evidence suggests that AT‐secreted molecules, known as adipokines, may reach the systemic circulation and interact with the BBB and the neurovascular system, compromising its integrity and potentially influencing the development of neurological disorders including AD (Pan & Kastin, 2007). Also, breakdown of the BBB is an important pathological feature in AD, worsening the clearance of amyloid‐β (Aβ) peptides, microglial activation and astrogliosis (Sousa et al, 2023).…”
Section: Cerebrovascular System Adipose Tissue and Alzheimer's Diseasementioning
confidence: 99%
“…Another genetic risk factor for AD is formin-related protein 2 (FMNL2), an astrogliaexpressed protein instrumental in glia-vasculature interactions and Aβ regulation [183]. Research indicated an elevated FMNL2 expression in both AD and cerebrovascular pathology [184]. Vascular risk factors amplify FMNL2 expression in AD patients, suggesting its pivotal role in exacerbating the AD pathology and vascular anomalies [185].…”
Section: Bbb Breakdown Mechanismsmentioning
confidence: 99%
“…This amide enhances functional CBF responses following brain stimulation and cognitive processes and diminishes brain Aβ concentrations in an AD mouse model, specifically the APPsw−/+ mice [194]. Nevertheless, a Phase III clinical trial with a RAGE inhibitor (NCT02080364) was terminated due to its low efficacy [184]. Moreover, a randomized, double-blind, placebo-controlled study was conducted to assess PF-04494700, an oral RAGE inhibitor, in patients diagnosed with mild-to-moderate AD.…”
Section: The Bbb As a Therapeutic Targetmentioning
confidence: 99%